Strategies to reduce reliance on soya bean meal and palm kernel meal in livestock nutrition - J.M. Wilkinson; R.H. Young (Journal of Applied Animal Nutrition)
Greenhouse gas emissions and loss of wildlife habitats have stimulated growing global concern over the continued expansion of soya bean and palm oilseed production on land recently converted from forest and natural grasslands. This paper reviews the roles of soya bean meal and palm kernel meal in livestock nutrition, drawing on research data to explore the potential for their replacement in nutritionally balanced diets. Soya bean meal is a widely used livestock feed due to relatively high levels of total protein and essential amino acids. Palm kernel meal has been used for many years in compound feeds for ruminant livestock and as a supplement to grazed pasture in periods of drought. A range of alternative sources of protein is available to replace soya bean and palm kernel meals, e.g. protected rapeseed meal can replace soya bean meal in diets for productive dairy cows, but constraints to widespread adoption include insufficient supply, anti-nutritional factors which require feeds to be processed or supplemented with enzymes, and imbalances in essential amino acids. Soya ‘milk’ made directly from soya beans is a less efficient process than producing milk from dairy cows, especially when they are grazed on pastures or given diets that do not contain soya bean meal.